PERKEMBANGAN DAN FAKTOR YANG MEMPENGARUHI PRODUKSI SUSU SAPI PERAH - andriyanto, wawan (Berkala Ilmiah AGRIDEVINA, 2019)
This study aims to analyze the development of dairy milk production in East Java and factors which influence the dairy milk production in East Java. Secondary Data is used and it taken from Livestock Agency and Statistical Centre Agency. The analysis is done using a linear regression trend analysis and multiple. From the results it was concluded that development of dairy cattle milk production from the year 2007-2015 always increased average 469,596,530 liters or increased by 3,6%. Factors that influence the production of livestock populations, namely a positive effect against cow’s milk production where the value of the sig 0,014<0,05. Milk prices a positive effect against cow’s milk production where the value of the sig 0,001 <0,05. Number of dairy cow milk companies a positive effect against cow’s milk production where the value of the sig 0,000 < 0,05. Analysis in test for simultaneous trials simultaneously factor population of cattle, cow’s milk prices, the number of dairy cow milk of positive effect on the development of dairy farmers’ milk production dairy cows in East JavaDOI : https://doi.org/10.33005/adv.v8i1.1614